(untitled) (CIPEEX, 2025)
The present study aims to analyze the phenomenon of moral harassment in the workplace, identifying its main characteristics, the consequences for victims and organizations, in addition to proposing preventive measures and measures to combat this practice. The study also aims to highlight the psychological, social and legal impact of moral harassment on workers. The research methodology was bibliographical review, through literature review, using scientific articles, official data and reports from organizations that work in the academic production of workers’ rights. The results indicate that moral harassment manifests itself in the work environment, with prolonged behaviors that humiliate, destabilize or isolate the employee. These behaviors can be subtle or explicit, such as insults, intimidation, overwork or even deliberate exclusion. The study revealed that victims of bullying suffer stress, anxiety and depression, which can lead to severe mental illness, as well as absences, sick leave and even resignations. In the field of organizations, moral harassment results in increased absenteeism, high employee turnover and deterioration of the organizational climate. It was also found that companies that do not address this problem face a serious weakening of their public image. The study concludes that bullying is a serious problem in the workplace, with profound impacts on both individuals and organizations. Through the implementation of effective prevention policies, such as the creation of safe reporting channels, training on conduct and organizational culture to value and respect dignity in the workplace. Furthermore, it is essential that companies face the problem head-on, shutting down aggressors and promoting a safe and risk-free working environment.